1993
DOI: 10.1212/wnl.43.11.2193
|View full text |Cite
|
Sign up to set email alerts
|

Sensory neuropathy associated with Dursban (chlorpyrifos) exposure

Abstract: Chlorpyrifos (Dursban) is an organophosphate insecticide with extensive domestic and agricultural applications. It is regarded as safe for these purposes; one report of neurotoxicity is attributed to massive ingestion in a suicide attempt. We report eight people who developed peripheral neuropathy after exposure to exterminator-applied commercial Dursban; five also experienced memory loss and cognitive slowing. Evaluation failed to reveal other causes of neurologic dysfunction; symptoms recurred in one patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(56 citation statements)
references
References 0 publications
4
51
0
1
Order By: Relevance
“…The study also provided important insight into the profile of neurotoxicity, which confirmed earlier findings and showed that there was a positive correlation between abnormal neurological tests and evidence of anxiety and depression in patients exposed to OP. In another study , the neuropathy profile confirmed earlier observations (Kaplan et al, 1993;Steenland et al, 1994;McConnell et al, 1994;Horowitz et al, 1999;Pilkington et al, 1999) that this neuropathy linked to LTLL exposure to OP, unlike OPIDN, was predominately involving the sensory nerve fibres and affected both small and large fibre populations. This neuropathy profile linked with LTLL exposure to OP was also compared with another one seen in chronic neurotoxicity following one or more acute cholinergic episodes ).…”
Section: Referencesupporting
confidence: 84%
See 1 more Smart Citation
“…The study also provided important insight into the profile of neurotoxicity, which confirmed earlier findings and showed that there was a positive correlation between abnormal neurological tests and evidence of anxiety and depression in patients exposed to OP. In another study , the neuropathy profile confirmed earlier observations (Kaplan et al, 1993;Steenland et al, 1994;McConnell et al, 1994;Horowitz et al, 1999;Pilkington et al, 1999) that this neuropathy linked to LTLL exposure to OP, unlike OPIDN, was predominately involving the sensory nerve fibres and affected both small and large fibre populations. This neuropathy profile linked with LTLL exposure to OP was also compared with another one seen in chronic neurotoxicity following one or more acute cholinergic episodes ).…”
Section: Referencesupporting
confidence: 84%
“…Analysis of all the above 11 studies show that neither the incidence nor the severity of development of chronic neurotoxicity had any relation with either the number nor the severity of the acute cholinergic episodes. In some of the cases described, the acute episodes were so mild that they escaped clinical detection (Kaplan et al, 1993;Jamal et al, 2001). …”
Section: Copind Following Acute Cholinergic Episodesmentioning
confidence: 96%
“…Some organochlorine insecticides such as chlorpyrifos reportedly cause both chronic neurologic symptoms (114) and modulation of the IRA (112). Certain OP insecticides enhance the large-fiber distal axonopathy caused by other OPs such as chlorpyrifos (109,114). Recently reported studies of GulfWar veterans confirm earlier reports of a connection between a syndrome of neurologic damage and wartime exposure to pesticides and insecticides (115)(116)(117)(118).…”
Section: Individual Ids Descriptionsmentioning
confidence: 53%
“…This interference may also extend to polychlorinated biphenyls (PCBs) (75) and in general to organophosphate (OP) and organochlorine compounds (113). Some organochlorine insecticides such as chlorpyrifos reportedly cause both chronic neurologic symptoms (114) and modulation of the IRA (112). Certain OP insecticides enhance the large-fiber distal axonopathy caused by other OPs such as chlorpyrifos (109,114).…”
Section: Individual Ids Descriptionsmentioning
confidence: 99%
“…In other study, no or mild changes which are in association with cholinergic overstimulation were reported in the patients. [8] Pesticide spraying process is associated with increased risk of neurotoxic effects on peripheral nerves, and the severity of poisoning depends on the dose and the type of organophosphate exposure. Chronic low-level exposure in non-poisoned subjects has been associated with impaired neurological functions, as documented in some epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%